Princípio de ação quântica de Schwinger - Melo, C.a.m. De [UNESP]; Pimentel, B.m. [UNESP]; Ramirez, J.a. [UNESP] (Sociedade Brasileira de Física, 2013)
The Schwinger quantum action principle is a dynamic characterization of the transformation functions and is based on the algebraic structure derived from the kinematic analysis of the measurement processes at the quantum level. As such, this variational principle, allows to derive the canonical commutation relations in a consistent way. Moreover, the dynamic pictures of Schrödinger, Heisenberg and a quantum Hamilton-Jacobi equation can be derived from it. We will implement this formalism by solving simple systems such as the free particle, the quantum harmonic oscillator and the quantum forced harmonic oscillator.

O princípio de ação quântica de Schwinger é uma caracterização dinâmica das funções de transformação e está fundamentado na estrutura algébrica derivada da análise cinemática dos procesos de medida em nível quântico. Como tal, este princípio variacional permite derivar as relações de comutação canônicas numa forma totalmente consistente. Além disso, propociona as descrições dinâmicas de Schrödinger, Heisenberg e uma equação de Hamilton-Jacobi em nível quântico. Implementaremos este formalismo na resolução de sistemas simples como a partícula livre, o oscilador harmônico quântico e o oscilador harmônico quântico forçado.
Schwinger quantum action principle
Keywords: mecânica quântica; princípio de ação quântica; princípios variacionais; quantum mechanics; quantum action principle; variational principles